Use, perception, and local management of Copernicia prunifera (Miller) H. E. Moore in rural communities in the Brazilian Savanna - José Afonso Santana de Almeilda; Nágila Alves Feitosa; Leilane de Carvalho e Sousa; Raimundo Nonato Oliveira Silva; Rodrigo Ferreira de Morais; Júlio Marcelino Monteiro; José Ribamar de Sousa Júnior (BMC, 2021)
Abstract Background Copernicia prunifera belongs to the Arecaceae family, and its production chain includes a set of economic activities based on the use of the stipe, petiole, fiber, fruits, roots, and leaves from which carnaúba wax is extracted, an economically valuable resource in the region. This study aimed to evaluate the uses, management, and perception of the species by local extractors. Methods Two communities were studied, Bem Quer, where 15 extractors of carnaúba leaves were interviewed, and Cana, where 21 extractors considered specialists were interviewed, totaling a sample of 36 interviewees. Interviewees were asked questions about uses, ways of handling, and perception of morphological variation in the carnaúba leaves. The number of leaves extracted and the income obtained from the sale of leaves were estimated from interviews and notes that each leader of extractors held during the year of the research and previous years, as well as direct observations made by researchers in the communities which recollection area of straw hold about 80 thousand individuals of C. prunifera. A regression analysis was used to explore the relationships between social variables (age, time in extractive activity, and income obtained from extraction) with the number of leaves exploited. Results The leaf was indicated as the most used part, from which an important powder is extracted for the production of wax. In addition, the leaf was also indicated to be used for fertilization and construction. The relationship between the socioeconomic variables, income from extraction, and the number of leaves extracted (in thousands) was significant (R 2 = 0.73 and p < 0.001). However, the other variables analyzed in this study, such as the time spent extracting leaves and the years of residence in the community (R 2 = 0.03 and p > 0.05); the number of leaves extracted and interviewee age (R 2= 0.05 and p > 0.05); and the number of leaves extracted and extraction time (R 2 = 0.04 and p > 0.05) did not indicate a relationship. Conclusion Local extractors observed that new leaves have the highest sales value, as they have the highest production of powder. In addition, economic factor is the preponderant force that directs the management strategies of native species. For this species, however, morphological and genetic studies are needed for further clarification.